Vers un contrôle bibliographique pour les lois du Québec - Le May, Denis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
This article attempts to demonstrate the need to enrich and to make explicit information contained in legislation in order to build an informative and easily retrievable legislative data base. Two methods of achieving this goal are proposed. First, it is suggested that the international standard bibliographic description (ISBD) be applied to legislative texts. Second, it is recommended that the methods and standards of the International Standardization Organization (ISO) be followed. These two proposals are considered the bare minimum for an efficient legislative data base.